Fertilizer combination effects on aggregate stability and distribution of aluminum and iron oxides. Issue 2 (9th February 2022) - Anthonio, Christian Kofi; Huang, Jing; Han, Tianfu; Qaswar, Muhammad; Liu, Kailou; Du, Jiangxue; Daba, Nano Alemu; Ali, Sehrish; Matelele, Lehlogonolo Abner; Liu, Shujun; Liu, Guangrong; Zhang, Huimin; et al.
Abstract: Background: One main anthropogenic activity through which aggregate stability and elements are impacted in soils is through fertilization. Inputs of phosphate fertilizers to soils, for instance, have direct impacts on other elements in soils. Organic fertilizer sources are also known to markedly influence the availability of microelements. However, the extent to which different combination ratios of organic and chemical fertilizers affect the availability of these microelements in paddy soil aggregates is not clear. Aim: Therefore, this study examined aggregate stability and the distribution pattern of various extractable aluminum, and iron oxides as influenced by a long‐term varied combinations of pig manure with chemical nitrogen, phosphorus, and potassium (NPK) fertilizer in a rice‐managed paddy. Method: Mehlich 3, dithionite, oxalate, and pyrophosphate solutions were used to extract oxides of Al and Fe in bulk soil, and aggregates under long‐term fertilizer combinations, which included unfertilized CK (control), chemical NPK, 30% chemical NPK + 70% pig manure, 50% chemical NPK + 50% pig manure, and 70% chemical NPK + 30% pig manure in a randomly complete block design. Results: The highest manure treatment (70% manure) markedly increased total organic carbon (TOC), and total nitrogen (TN) in contrast to other treatments. Soil pH was higher in all manure‐treated fertilizers than in chemical NPK fertilizer likely because organic matter (OM) neutralized the protons. Additionally, the highest manure treatment led to the creation of more macroaggregates (2–0.25 mm), which translated into higher aggregate stability indices such as mean weight diameter (MWD), and geometric mean diameter (GMD) compared to other treatments. It was also noted that the 70% manure treatment in comparison with other treatments, was associated with higher concentrations of extractable Al and Fe oxides. It was, however, not clear if the changes in extractable metals detected in this treatment resulted from OM‐driven redistribution of metals or if the manure contained some Al and Fe itself. Conclusion: The 70% manure treatment increased TOC, TN, pH, and aggregate stability indices (higher MWD and GMD). This fertilizer treatment was also associated with more extractable Al and Fe oxides. For more sustainable rice‐managed paddies, the 70% manure treatment should be considered over the other fertilizer combinations.